Turkish folk medicinal plants, Part IV: Gonen (Balikesir) - (:unkn) unknown (ELSEVIER SCIENCE BV, 2001)
Eighty-four folk medicinal plants from Gonen (Turkey) are reported. Among them 73 species are wild and 11 species are cultivated plants. The folk medicinal plants are mostly used for the treatment of hemorrhoids, rheumatism, stomach and kidney ailments. (C) 2001 Elsevier Science B.V. All rights reserved.
Keywords: folk medicine; medicinal plants; Turkey